Analytic methodology for demographic variation analyses for wave 1 of the global flourishing study - R. Noah Padgett; Matt Bradshaw; Ying Chen; Richard G. Cowden; Sung Joon Jang; Eric S. Kim; Koichiro Shiba; Byron R. Johnson; Tyler J. VanderWeele (BMC Global and Public Health)
Abstract In this article, we describe the statistical and design methodology of the demographic variation analyses used as part of a coordinated set of manuscripts for wave 1 of the Global Flourishing Study (GFS). Aspects covered include the following: evaluating demographic variation, accounting for the complex sampling design, missing data and imputation, and meta-analysis. We provide a brief illustrative example of the demographic variation analyses using a measure of purpose in life from the GFS survey and conclude by outlining some strengths and limitations of the analytic and statistical methodology employed.